KUALITAS PELAYANAN PRAMUWISATA LOKAL PADA OBJEK WISATA CANDI MUARA TAKUS KABUPATEN KAMPAR PROVINSI RIAU - Safitri, Nur; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Many people travel to improve their wellbeing perception and Indonesian society are no exception in that, they hope to enchance their quality of life through tourism.  As such, this study presents a examination the service quality of tour guide in Muara Takus Tempel, Kampar Regency, Riau Province. This study aims to determine the quality of local guide services at Muara Takus Temple, Kampar Regency, Riau Province. This study uses a mixed method to examine the issues raised above. This current study collected samples from 100 tourists who visited Muara Takus Temple. Tour guiding  issues  were  identified through a series of in-depth and focus interviews and integrating many secondary data. Afterwards for the data collection techniques this study used observation, questionnaires, interviews and documentation. The results of this research exhibit the service quality of local guide at Muara Takus Temple is good, but still need some improvement. This result made based on 5 dimensions, such as dimension of tangible, reliability, responsiveness, assurance and empathy. Keywords: Service Quality, Tour Guide, Muara Takus Temple